In vitro assessment of varying peptide surface density on the suppression of angiogenesis by micelles displaying αvβ3 blocking peptides. Issue 2 (30th August 2022) - Bhushan, Neha Phani; Stack, Trevor; Scott, Evan A.; Shull, Kenneth R.; Mathew, Benjamin; Bijukumar, Divya
Abstract: Ligand targeted therapy (LTT) is a precision medicine strategy that can selectively target diseased cells while minimizing off‐target effects on healthy cells. Integrin‐targeted LTT has been developed recently for angiogenesis‐related diseases. However, the clinical success is based on the optimal design of the nanoparticles for inducing receptor clustering within the cell membrane. The current study focused on determining the surface density of Ser‐Asp‐Val containing anti‐integrin heptapeptide on poly (ethylene glycol)‐ b ‐poly(propylene sulfide) micelles (MC) required for anti‐angiogenic effects on HUVECs. Varying peptide density on PEG‐ b ‐PPS/Pep‐PA MCs (Pep‐PA‐Peptide‐palmitoleic acid) was used in comparison to a random peptide (SGV) and cRGD (cyclic‐Arginine‐Glycine‐Aspartic acid) construct at 5%‐density on MCs. Immunocytochemistry using CD51/CD31 antibody was performed to study the integrin blocking by MCs. In addition, the expression of VWF and PECAM‐1, cell migration and tube formation was evaluated in the presence of PEG‐ b ‐PPS/Pep‐PA MCs. The results show PEG‐ b ‐PPS/SDV‐PA MCs with 5%‐peptide density to achieve significantly higher αvβ3 blocking compared to random peptide as well as cRGD. In addition, αvβ3 blocking via MCs further reduced the expression of vWF and PECAM‐1 angiogenesis protein expression in HUVECs. Although a significant level of integrin blocking was observed for 1%‐peptide density on MCs, the cell migration and tube formation were not significantly affected. In conclusion, the results of this study demonstrate that the peptide surface density on PEG‐ b ‐PPS/Pep‐PA MCs has a significant impact in integrin blocking as well as inhibiting angiogenesis during LTT. The outcomes of this study provides insight into the design of ligand targeted nanocarriers for various disease conditions.